Family Support as a Determinant of Motivation in Early Childhood English Learning - Ratnadi, Ni Nyoman Ari (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
Early childhood represents a critical period for language acquisition and motivational development, where family support plays a pivotal role. This study investigates the relationship between family support and English learning motivation among early childhood students in Group B of Triamerta Singaraja Kindergarten, Indonesia. Using a cross-sectional analytical survey method, data were collected from 69 respondents through validated questionnaires. The Spearman Rank correlation test revealed a significant positive relationship between family support and learning motivation (r = 0.623, p < 0.05). The findings indicate that children with more excellent family support exhibit higher motivation levels, underlining the importance of parental involvement in fostering effective bilingual education. This research contributes to the growing literature on early childhood education by providing actionable insights into how family engagement can enhance language acquisition and learning outcomes. Future studies should explore intervention strategies tailored to diverse socio-cultural contexts to optimize early learning experiences.